Acknowledgements 2023 - EJHC Management Team (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
In this editorial, we look back at 2023 and want to acknowledge and thank all those who have contributed to the European Journal of Health Communication by reviewing submissions, serving as editors, or submitting their work.